2022
DOI: 10.1016/j.psychsport.2021.102106
|View full text |Cite
|
Sign up to set email alerts
|

Identity leadership and social identification within sport teams over a season: A social network analysis

Abstract: Objectives: This study explored the relationships between identity leadership and social identification in sport teams over the course of a season using social network analysis.Methods: Participants from 23 competitive sport teams (N = 388, Mage = 20.7 years) indicated the extent to which each of their teammates displayed various forms of identity leadership (i.e., identity prototypicality, identity advancement, identity entrepreneurship, identity impresarioship) and the extent to which these same teammates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Further, our findings suggest that digital leadership is evident at different organizational levels, such as the board of directors, senior and upper-level leaders, and IT leadership. These conclusions are supported by studies conducted by Karippur and Balaramachandran (2022), Klus and Müller (2021), Petry (2018), El Sawy et al (2013), Temelkova (2018), Bruner et al, (2022), Frankowska and Rzeczycki (2020), and Shah and Patki (2020). In addition, the firm's size also played a crucial role in managing sustainable organizational performance.…”
Section: Discussionmentioning
confidence: 66%
“…Further, our findings suggest that digital leadership is evident at different organizational levels, such as the board of directors, senior and upper-level leaders, and IT leadership. These conclusions are supported by studies conducted by Karippur and Balaramachandran (2022), Klus and Müller (2021), Petry (2018), El Sawy et al (2013), Temelkova (2018), Bruner et al, (2022), Frankowska and Rzeczycki (2020), and Shah and Patki (2020). In addition, the firm's size also played a crucial role in managing sustainable organizational performance.…”
Section: Discussionmentioning
confidence: 66%
“…As a result, these specific six items have not been previously validated. Bruner et al (2022) recommended this approach when conducting SNA. The present study used both visual and quantitative SNA techniques to assess the team's athlete leadership and cohesion relationships as well as the relationships between attribute data and the networks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, relationships between attribute data of self-rated athlete leadership behaviour and network athlete leadership, as nominated by one's teammates has not been previously examined. While researchers have explored the associations between different athlete leadership networks such as different athlete leadership roles (task, motivation, social, and external;Fransen et al, 2015), and dimensions of identity leadership (prototypicality, advancement, entrepreneurship, and impresarioship;Bruner et al, 2022), no current research has simultaneously examined self-reported athlete leadership and peer reported network athlete leadership. Assessing the difference between self-reported (attribute) and other-reported (network) leadership is of interest because previous literature has found discrepancies between these two types of information (e.g., Branson and Cornell, 2009;Yeatman and Trinitapoli, 2011), which may be due to factors such as social desirability bias (Gould, 1969) over-estimating one's own characteristics (An, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The average time between questionnaire completion ranged from 4 to 22 weeks 1 , with an average of 19 weeks. Of particular importance within the larger research project is the fact that the hypotheses tested in this paper were unique in both operationalisation of constructs and study methodology (see also Bruner et al, 2022).…”
Section: Methodsmentioning
confidence: 99%